PENTINGNYA DATA INTEGRASI DALAM PENGEMBANGAN SISTEM INFORMASI DI BIDANG PENDIDIKAN - Umi Nur Habibah; Muhammad Irwan Padli Nasution (JURNAL ILMIAH NUSANTARA, 2024)
In today's modern era, the development of information systems in the field of education increasingly requires accurate data integration. This journal discusses the importance of data integration in improving the efficiency, accuracy, and effectiveness of information systems in the field of education. The purpose of this writing is to assist the education sector in implementing integrated information systems to process data, make decisions, and improve the quality of information services. In addition, data integration in application usage can also provide up-to-date information to users. Data integration in the field of education can improve the quality of education, make educational institutions more creative, responsive and dynamic, and make students inspired to create the best collaboration between information technology and education.